Religiosity of the crime novel. Theoretical reflections concerning some (impious?) Literary genre - Brylla, Wolfgang (Acta Universitatis Lodziensis. Folia Germanica, 2016)
The aim of the following paper was to analyse the history of crime literature genre – which is perceived in the terms of kitsch and structural conventionality – from the perspective of religious morality, ethics and aesthetics, in order to show that between theology and bloody crime fiction there are many similarities. Criminal poetry is not only close to the Bible and Christian philosophy in respect of the subject matter or used motives, but also in regard to the conceptual narrative means that were used. One can even venture the statement that crime novel – this term stands for its various variants – on the one hand derives from the biblical theology, on the other hand creates a kind of “new Bible” on his own and a specific religion: the so-called religion in-between, religion between impious crime and pious crime solving.